Assessment of the ovarian reserve in a group of perimenopausal women - Korabel, Joanna; Krzysiek, Józef (Menopause Review/Przegląd Menopauzalny, 2013)
Assessment of the ovarian reserve is all the time a challenge for many clinicians. Although there are many methods used in clinical practice, we still do not have one, simple and reliable method. This is particularly relevant in the present social climate, when increasing numbers of women are deferring childbearing. The decline in fecundity with the age of a woman is mainly attributed to the loss of follicles from the ovary and a decrease in oocyte quality. Evaluation of the aging status of the ovary in an individual woman has been hampered by the lack of knowledge with regard to the contribution of these two factors. Very often the ovarian reserve is the main factor influencing results of assisted reproductive techniques. IVF treatment is both expensive and stressful for patients. The expected chances of achieving a successful pregnancy are crucial in the decision as to whether an infertile couple should embark on IVF treatment. The ovarian reserve significantly influences IVF outcome. Hypoestrogenism connected with the aging can have future influence on the health status. Besides low potential of reproduction, low estrogen level may have bad correlations with cardiovascular diseases and increase the risk of osteoporosis. Although there are many diagnostic methods, we still do not have one, simple and reliable method. The ideal method will be the response of the ovary to the standard ovulation protocol.